1988
DOI: 10.1007/bf02535598
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipids in spontaneously hypertensive rats and sprague‐dawley rats fed menhaden oil

Abstract: Dietary n-3 fatty acids, abundant in fish oil, exert a variety of effects that attenuate cardiovascular disease. In this study, we assessed the effect of fish oil (menhaden oil) on the serum lipid profile in hypertensive and normotensive rats. Spontaneously hypertensive rats (SHR) or Sprague-Dawley rats (SD) were fed either standard powdered diet (L-485), or L-485 + 5% menhaden oil (MO) or L-485 + 5% corn oil (CO) from weaning through eight months of age. Systolic blood pressure (BP) was periodically determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Data of the present studies, therefore, can be interpreted that the level of dietary supplementation , 6g %, might have been insufficient to exert significant influence upon the blood pressure of SHR. This interpretation is in accord with the report by Kingsley and Snyder, who fed SHR a diet containing 5% fish oil and did not observe a decrease of blood pressure (30).…”
Section: Discussionsupporting
confidence: 92%
“…Data of the present studies, therefore, can be interpreted that the level of dietary supplementation , 6g %, might have been insufficient to exert significant influence upon the blood pressure of SHR. This interpretation is in accord with the report by Kingsley and Snyder, who fed SHR a diet containing 5% fish oil and did not observe a decrease of blood pressure (30).…”
Section: Discussionsupporting
confidence: 92%
“…Watanabe et al (1989) found that high w-6 or high w-3 diets had no effect on the development of hypertension in male SHR. Kingsley and Snyder (1988) found that neither the degree of hypertension nor the plasma lipid profile varied in SHR fed w-3 or w-6 diets for 8 months. Croft et al (1988) found a pressor effect of fish oil supplementation during the first week if the animals were salt-loaded.…”
Section: Discussionmentioning
confidence: 81%
“…Overall, the effects of high PUFA intakes on blood pressure remain controversial in human studies as well as in animal models. Increased dietary PUFA have been reported by some investigators to decrease blood pressure in spontaneously hypertensive rats (SHR; Hoffmann et al 1986;Mtabaji et al 1988;Von Au et al 1988;Bayorh et al 1989;Karanja et al 1989;Brandle & Jacob, 1990;Yin et al 1990;Engler et al 1992); however, others find no significant effects or actual increases in blood pressure (McGreger et al 1981;Codde et al 1989;Croft et al 1988;Kingsley & Snyder 1988;Watanabe et al 1989). Since hypertension is one of the risk factors for developing coronary heart disease, many people are motivated to increase dietary PUFA to achieve the cardiovascular beneficial effects.…”
mentioning
confidence: 99%
“…Several factors might be involved in the observed discrepancies. Firstly, the SD rat is more susceptible to changes in lipid profile upon feeding different diets than is the SHR [55] . Dose and duration of administered diets are other factors which may further affect the outcome.…”
Section: Discussionmentioning
confidence: 99%